Genicular Nerve Radiofrequency Ablation and Dual Subsartorial Block for Chronic Knee Pain Post Total Knee Replacement: A Case Report - Aidyl Fitrisyah; Stevanus Eliansyah Handrawan; Nurlaili Maya Ramadhanty (HM Publisher, 2021)
Introduction. Chronic pain defines as pain persisting for three months or longer, chronic post-surgical pain can affect all dimensions of health-related quality of life, and is associated with functional limitations. treatment of chronic pain after total knee replacement is challenging, and evaluation of combined treatments and individually targeted treatments matched to patient characteristic. Genicular nerve block radiofrequency ablation is a safe and effective therapeutic procedure for pain associated with chronic pain due to knee osteoarthritis, and the evolution of newer regional analgesia techniques aids in reducing postoperative pain Dual Subsartorial Block (DSB) as a procedure specific, post total knee replacemet. historically there has been a reliance on using a pain-spesific assessment tools Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) Case Presentation. A 55-year old woman admitted she had pain on bilateral knee, the knee pain had affected her daily living, she was diagnosed with chronic knee pain post TKR because of osteoarthritis genu bilateral, the patient was planning genicular nerve radiofrequency ablation and dual subsartorial block, from the examination we found that numeric rating scale was 6 (moderate pain) with WOMAC score 76, before the procedure the patients are examined through radiology for any deformity in the knee. The genicular nerve radiofrequency ablation under ultrasound guidance on bonylandmark, resulting anesthesia of the anterior compartment of the knee, and dual subsartorial block that cover almost all the innervations of pain generating component of the anterior and posterior knee joint involved in TKR surgery. After the procedure we reevaluated the pain score using NRS was 2 (mild pain), and with WOMAC Score 19. Conclusion. Treatment of chronic pain post total knee replacemet was challenging, targeted treatment may ameliorate the pain and prevent long term disability.